Theories of Impression Making and their Rationale in Complete Denture Prosthodontics - Dwivedi, Alok; Vyas, Rajesh (Journal of Orofacial Research, 2013)
Theory means observation based on principles and concept is the application of these theories. Impression forms an important virtue for the success of complete denture treatment and hence the concepts of impression should be properly understood. The importance of the in-depth study of history of impression making for complete dentures lies in the thorough understanding of different types of techniques and theories proposed from time to time.